Hepatitis B virus and Homo sapiens proteomewide analysis: A profusion of viral peptide overlaps in neuron-specific human proteins - Rosalia Ricco (Dove Medical Press, 2010)
Rosalia Ricco1, Darja Kanduc21Department of Pathological Anatomy, 2Department of Biochemistry and Molecular Biology, University of Bari, Bari, ItalyAbstract: The primary amino acid sequence of the hepatitis B virus (HBV) proteome was searched for identity spots in the human proteome by using the Protein Information Resource database. We find that the HBV polyprotein shares sixty-five heptapeptides, one octapeptide, and one nonapeptide with the human proteins. The viral matches are disseminated among fundamental human proteins such as adhesion molecules, leukocyte differentiation antigens, enzymes, proteins associated with spermatogenesis, and transcription factors. As a datum of special interest, a number of peptide motifs are shared between the virus- and brain-specific antigens involved in neuronal protection. This study may help to evaluate the potential cross reactions and side effects of HBV antigen-based vaccines.Keywords: HBV proteome, human proteome, similarity analysis, viral versus human proteome overlapping, vaccine-related cross-reactions